BRG1 promotes liver cancer cell proliferation and metastasis by enhancing mitochondrial function and ATP5A1 synthesis through TOMM40 - Yongfeng Hui; Junzhi Leng; Dong Jin; Genwang Wang; Kejun Liu; Yang Bu; Qi Wang (Cancer Biology & Therapy)
Hepatocellular carcinoma (HCC) is one of the most lethal malignant tumors worldwide. Brahma-related gene 1 (BRG1), as a catalytic ATPase, is a major regulator of gene expression and is known to mutate and overexpress in HCC. The purpose of this study was to investigate the mechanism of action of BRG1 in HCC cells. In our study, BRG1 was silenced or overexpressed in human HCC cell lines. Transwell and wound healing assays were used to analyze cell invasiveness and migration. Mitochondrial membrane potential (MMP) and mitochondrial permeability transition pore (mPTP) detection were used to evaluate mitochondrial function in HCC cells. Colony formation and cell apoptosis assays were used to evaluate the effect of BRG1/TOMM40/ATP5A1 on HCC cell proliferation and apoptosis/death. Immunocytochemistry (ICC), immunofluorescence (IF) staining and western blot analysis were used to determine the effect of BRG1 on TOMM40, ATP5A1 pathway in HCC cells. As a result, knockdown of BRG1 significantly inhibited cell proliferation and invasion, promoted apoptosis in HCC cells, whereas BRG1 overexpression reversed the above effects. Overexpression of BRG1 can up-regulate MMP level, inhibit mPTP opening and activate TOMM40, ATP5A1 expression. Our results suggest that BRG1, as an oncogene, promotes HCC progression by regulating TOMM40 affecting mitochondrial function and ATP5A1 synthesis. Targeting BRG1 may represent a new and effective way to prevent HCC development.